2009
DOI: 10.1111/j.1749-6632.2008.03672.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Duplications of Opioid Receptor and Peptide Genes in Vertebrate Evolution

Abstract: The opioid receptor family in mammals has four members called delta, kappa, mu, and NOP (the nociceptin/orphanin receptor). We show here that they arose from a common ancestral gene through quadruplication of a large chromosomal region, presumably in the two basal vertebrate tetraploidizations. The four opioid peptide precursor genes have a more complicated evolutionary history involving chromosomal rearrangements but nevertheless seem to have arisen in the same time period as the receptors. Thus the system of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…In vertebrates, nonneuronal functions of serotonin include craniofacial development and left-right asymmetry (Levin et al., 2006; Reisoli et al., 2010). The opioid system appeared about 450 million years ago with the emergence of gnathostomes (Larhammar et al., 2009), whereas other neuropeptides were already present earlier (Coates et al., 2000; Elphick, 2010; Elphick and Thorndyke, 2005; Hauser et al., 2006, 2008). Our findings define unexpected functions for SST and Noc signaling in vertebrate embryos outside the CNS, where they influence cell fate and tissue morphogenesis, suggesting that these may be the ancestral roles of these small molecules, whose functions in the nervous system were co-opted much later during evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, nonneuronal functions of serotonin include craniofacial development and left-right asymmetry (Levin et al., 2006; Reisoli et al., 2010). The opioid system appeared about 450 million years ago with the emergence of gnathostomes (Larhammar et al., 2009), whereas other neuropeptides were already present earlier (Coates et al., 2000; Elphick, 2010; Elphick and Thorndyke, 2005; Hauser et al., 2006, 2008). Our findings define unexpected functions for SST and Noc signaling in vertebrate embryos outside the CNS, where they influence cell fate and tissue morphogenesis, suggesting that these may be the ancestral roles of these small molecules, whose functions in the nervous system were co-opted much later during evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis suggests two rounds of genome-wide duplication (paleoploidization) from a single ancestral opioid gene (unireceptor) (Ohno, 1999;Escriva et al, 2002;Lundin et al, 2003), with the first yielding the ancestral DOR-1/MOR-1 and ORL-1/KOR-1 genes. The duplication then led to DOR-1 and MOR-1, as well as KOR-1 and ORL-1 (Dreborg et al, 2008;Larhammar et al, 2009;Stevens, 2009). The predicted MOR-1 protein sequences from 27 species reveals four major clades as follows: 1) fish, 2) amphibians, 3) birds, and 4) mammals, mimicking the evolutionary tree of life (Fig.…”
Section: B Phylogeny and Evolutionmentioning
confidence: 99%
“…The specific pairing of MOR with DOR, and KOR with ORL on separate branches of the sequence tree is supported by a genomic study whereby the greatest number of gene duplicates was found between paralogous regions on chromosomes 1 and 6, and between paralogous regions on chromosomes 8 and 20 (McLysaght et al, 2002). Evidence for 2R duplication of the family of opioid receptor genes (and endogenous opioid peptides) is also supported by studies of chromosomal synteny (Dreborg, Sundstrom, Larsson, & Larhammar, 2008;Josefsson, 2000;Larhammar, Dreborg, Larsson, & Sundstrom, 2009;Lundin et al, 2003;Sundstrom, Dreborg, & Larhammar, 2010).…”
Section: Duplicated Opioid Family Receptor Genes In the Human Genomementioning
confidence: 79%